Digital Forensic Analysis on Android Smartphones for Handling Cybercrime Cases - Firmansyah Gustav Hikmatyar; Bambang Sugiantoro (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
As the times progressed, forensic science has developed rapidly. The science of forensics extends to new areas of technology ranging from digital forensics, computer forensics and mobile forensics. Mobile forensics in analyzing and collecting data is obtained from various resources, such as operating systems, communication lines and also various storage media. The most popular mobile operating system of the day is a smartphone based on android operating system. With android technology, criminals can use that technology as a crime medium ranging from overriding crime ideas, crime targets and crime scenarios. In this Final Project use forensic mobile application to get data residing in cell phone actors, in the form of text, sound, picture and video that have or not yet deleted in smartphone. In this study, a model for investigating the crime scene is the author using the Generic Computer Forensic Investigation Model (GCFIM). On the GCFIM model the investigator may be able to return to the previous stage because of the possibility of a changeable situation (both physical and digital), the investigation tools used, the crime tools used, and the level of investigative expertise. In this research also added weighting method of word TF-IDF, where this method can help to find keyword in digital evidence in the form of word / text.